2023
DOI: 10.1126/science.adf0419
|View full text |Cite
|
Sign up to set email alerts
|

Obligate chimerism in male yellow crazy ants

Abstract: Multicellular organisms typically develop from a single fertilized egg and therefore consist of clonal cells. We report an extraordinary reproductive system in the yellow crazy ant. Males are chimeras of haploid cells from two divergent lineages: R and W. R cells are overrepresented in the males’ somatic tissues, whereas W cells are overrepresented in their sperm. Chimerism occurs when parental nuclei bypass syngamy and divide separately within the same egg. When syngamy takes place, the diploid offspring eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, there are also more radical forms, where cells from once distinct zygotes now share the same body, a process known as chimerism (Rinkevich, 2011). Whilst such chimeras are relatively rare, they are found across the tree of life, from corals and monkeys to algae, ants, and even ourselves (Ross et al, 2007;Boddy et al, 2015;Santelices et al, 2017;Chang et al, 2018;Guerrini et al, 2021;Darras et al, 2023). Moreover, new genomic tools have opened new windows into these phenomena across a range of different species, giving us a richer picture not only of the frequency of chimerism, but also its genetic structure within organisms (del Rosario et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also more radical forms, where cells from once distinct zygotes now share the same body, a process known as chimerism (Rinkevich, 2011). Whilst such chimeras are relatively rare, they are found across the tree of life, from corals and monkeys to algae, ants, and even ourselves (Ross et al, 2007;Boddy et al, 2015;Santelices et al, 2017;Chang et al, 2018;Guerrini et al, 2021;Darras et al, 2023). Moreover, new genomic tools have opened new windows into these phenomena across a range of different species, giving us a richer picture not only of the frequency of chimerism, but also its genetic structure within organisms (del Rosario et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…220–235). In biology, the term chimera has been used to designate real beings with multiple genomes coexisting in one body, that is, real‐life chimeras (Darras et al, 2023; Khan et al, 2004; Kinder et al, 2017; Yu et al, 2002). Microbiology has also discovered phenomena of encounter between distinct and possibly very heterogenous genetic materials that create chimeras: for example, it has been shown that mitochondria, the intracellular organelles found in all eukaryotic organisms (animals, plants, fungi, etc.…”
Section: Introduction—learning Strategies In the Unknown: The Explora...mentioning
confidence: 99%